ETIKA MENGAJAR DI ERA KOLABORASI - SYARIFAH RAHMI (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
We live in an era of moral crisis that has hit the younger generation without ethical education from an educator. ethics is an implementation of one's behavior and attitude which is one of the important pillars that will determine one's achievements and achievements. And ethics that greatly affect students is the ethics of a teacher or educator. Where when in the school environment or in the place of education will be emulated by all behaviors because life in the school environment is more than at home. In fact, some students who when successful admit that a lot more influences their success are teachers, lecturers and others. It becomes an obligation for a teacher to have an educating spirit with an effort to succeed in education specifically and develop civilization in general by holding the principle that we live in an age of collaboration not in the age of competition, so that what we do is not because we want to win alone.